Awareness of breast cancer incidence and risk factors among healthy women in Germany: an update after 10 years - Poehls, Uwe G.; Hack, Carolin; Wunderle, Marius; Renner, Stefan P.; Lux, Michael P.; Beckmann, Matthias; Fasching, Peter; Nabieva, Naiba (European Journal of Cancer Prevention, 2019)
Early breast cancer detection programs depend for effectiveness on the participation rate, which is affected by risk factor awareness. This study investigated changes in women's risk factor awareness between 2004 and 2016. Results from a 2004 survey of 2107 healthy women were compared with new data obtained using the same questionnaire in 2016, with 866 participants indicating their knowledge and perceptions regarding breast cancer incidence, risk factors, risk perceptions, and levels of concern. Logistic regression models assessed the influence of time point (2004 vs. 2016) on correct recognition of risk factors such as age at first childbirth, childlessness, lack of breastfeeding, hormone replacement therapy (HRT), and family history. Regression models were adjusted for common sociodemographic characteristics. Reproductive risk factors were regarded as influencing breast cancer risk less often. In 2004, age at first birth, childlessness, and lack of breastfeeding were regarded as risk factors by 24, 32, and 37%, respectively, in comparison with only 15, 18, and 23% in 2016. All changes were statistically significant. Awareness of HRT as a risk factor increased significantly (36-57%), and family history was recognized as a risk by 75 and 73% in 2004 and 2016, respectively. Most women recognized family history as a breast cancer risk factor. This did not change, reflecting the topic's media prominence. Awareness of HRT as a risk factor increased, probably owing to public information after the large HRT studies. It is unclear why reproductive risk factors are less frequently recognized; educational programs should address this information deficit.
CRIS-Team Scopus Importer:2019-10-08